Strategi manajemen dalam mempertahankan keberlanjutan BLKK pesantren di Jawa Timur - Dede Nurohman; Risdiana Himmati (Nur Science Institute, 2025)
Indonesia's new economic current positions Islamic boarding schools (pesantren) as the epicenter of national economic growth. Through the Islamic Boarding School Community Job Training Center (BLKK) program, Islamic boarding schools are expected to become economic drivers for lower-class communities. This paper examines the extent to which the BLKK Islamic boarding school programs, provided by the Ministry of Manpower, can contribute to and maintain the economic independence of Islamic boarding schools and communities. This study is a field study using a qualitative approach. The research was conducted at seven BLKK Islamic boarding schools in four regions: Kediri, Blitar, Jombang, and Trenggalek. The study identified three factors that play a significant role in determining the sustainability of the Islamic boarding school empowerment process through the BLKK. These three things are: the charisma of the Kiai (Islamic) is well maintained and productive, the role of alumni is well managed, and there is external collaboration between the Islamic boarding school and external institutions.